Merging timescale for the supermassive black hole binary in interacting galaxy NGC 6240 - Sobolenko, Margaryta; Berczik, Peter; Spurzem, Rainer (Astronomy and astrophysics, 2021)
Context. One of the mechanisms leading to the creation of a supermassive black hole (SMBH) is the so-called hierarchical merging scenario. Central SMBHs at the final phase of interacting and coalescing host-galaxies are observed as SMBH binary (SMBHB) candidates at different separations from hundreds of parsecs to megaparsecs. Aims. Today one of the strongest SMBHB candidates is the ultraluminous infrared galaxy NGC 6240 which was spatially and spectroscopically resolved in X-rays by Chandra. Dynamical calculation of central SMBHBs merging in a dense stellar environment allows us to retrace their evolution from kiloparsec to megaparsec scales. The main goal of our dynamical modeling was to reach the final, gravitational wave emission regime for the model BHs. Methods. We present direct N-body simulations with up to one million particles and relativistic post-Newtonian corrections for the SMBH particles up to 3.5 post-Newtonian terms. Results. Generally speaking, the set of initial physical conditions can strongly affect our merging time estimations. However, within a certain range of our parameters, we do not find any strong correlation between merging time and BH-to-BH mass or BH-to-bulge mass ratios. Varying the numerical parameters (like particle number - N) does not significantly change the merging time limits. From our 20 models, we find an upper limit on the merging time for central SMBHBs of less than ∼55 Myr. This precise number is only valid for our combination of initial mass ratios. Conclusions. Further detailed research of rare dual and multiple BHs in dense stellar environments (based on observational data) could clarify the dynamical co-evolution of central BHs and their host-galaxies.
Gesehen am 05.11.2021